Against Common Assumptions, the World's Shark Bite Rates Are Decreasing. (2nd June 2019) - Ritter, Erich; Amin, Raid; Cahn, Kevin; Lee, Jonathan
Abstract : The trends of the world's top ten countries relating to shark bite rates, defined as the ratio of the annual number of shark bites of a country and its resident human population, were analyzed for the period 2000-2016. A nonparametric permutation-based methodology was used to determine whether the slope of the regression line of a country remained constant over time or whether so-called joinpoints, a core feature of the statistical software Joinpoint, occurred, at which the slope changes and a better fit could be obtained by applying a straight-line model. More than 90% of all shark bite incidents occurred along the US, Australia, South Africa, and New Zealand coasts. Since three of these coasts showed a negative trend when transformed into bite rates, the overall global trend is decreasing. Potential reasons for this decrease in shark bite rates—besides an increase in the world's human population, resulting in more beach going people, and a decrease of sharks due to overfishing—are discussed.